FAWASIL OF THE QUR'ANIYAH IN QS. AL-INSYIRAH: ANALYSIS OF THE BEAUTY OF RHETORIC QS. AL-INSYIRAH - Mainaki, Taufik Ruudyan (Al-Imtaz: Jurnal Keilmuan Ushuluddin, 2024)
The Qur'an, as the Divine revelation, possesses unparalleled linguistic beauty, where every element of language functions not only to convey a message but also to evoke awe through its structure and rhythm. One of the key elements contributing to this beauty is the fawasil of the verses (the closure of the verses). This study focuses on the rhetorical beauty of the fawasil in Surah Al-Insyirah, which has unique characteristics in terms of diction, rhythm, and phonetic harmony. The methodology used is a descriptive-analytical literature review, analyzing data from relevant sources along with theories of balaghah (rhetoric) and rhetoric in the Qur'an. The focus of this research is to explore how the rhetorical structure of the fawasil in Surah Al-Insyirah not only serves as a verse closure but also enriches the meaning and provides a profound emotional impact on the reader or listener. The results show that the fawasil in Surah Al-Insyirah contain extraordinary rhythm and sound harmony, which further emphasize the power of the Qur'anic language in delivering the Divine revelation. This rhetorical beauty not only creates phonetic harmony but also strengthens the message and meaning contained in each verse. Therefore, this study contributes to a deeper understanding of the rhetorical power in the Qur'an, specifically in the fawasil of Surah Al-Insyirah, demonstrating that the Qur'anic language is not merely a tool of communication but also an exceptional and unparalleled work of literature.